2015
DOI: 10.2119/molmed.2015.00099
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Acute Intermittent Porphyria: Biochemical and Pathologic Studies of the Explanted Liver

Abstract: Acute intermittent porphyria (AIP), the most common acute hepatic porphyria, is an autosomal-dominant disorder due to the half-normal activity of the heme biosynthetic enzyme, hydroxymethylbilane (HMB) synthase (1). Symptomatic heterozygotes, most (~90%) of which are women, experience episodic life-threatening acute neurovisceral attacks that typically begin with severe abdominal pain and may include hypertension, tachycardia, constipation, motor weakness and seizures. These attacks are precipitated by certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“… showed that during intravascular hemolysis leading to free haem excess, the liver is the most susceptible organ to haem overload, and when hemopexin capacity is exceeded, haem accumulates mainly in Küpffer cells. In line with our results, three well‐documented studies concerning recurrent AIP patients reported also that regular hemin infusions trigger variable liver iron overload .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… showed that during intravascular hemolysis leading to free haem excess, the liver is the most susceptible organ to haem overload, and when hemopexin capacity is exceeded, haem accumulates mainly in Küpffer cells. In line with our results, three well‐documented studies concerning recurrent AIP patients reported also that regular hemin infusions trigger variable liver iron overload .…”
Section: Discussionsupporting
confidence: 92%
“…The pathogenesis of the acute attacks is hypothesized to result from an overproduction of a hepatic neurotoxic metabolite, presumably d-aminolevulinic acid (ALA) [3,4]. This notion is consistent with the correction of the disease by liver transplantation in patients with severe AIP [5][6][7][8][9]. Moreover, when domino liver transplantations were performed, the recipients developed biological and clinical acute porphyric attacks [10].…”
Section: Introductionmentioning
confidence: 80%
“…1, 19 An analysis by Singal et al 1 reported that as of 2014, of the 14 known AIP liver transplant patients, bile leak was recorded for 1, renal dysfunction for 2, and hepatic artery thrombosis for 4. Yasuda et al 20 performed a review which showed that HAT was not seen at therapeutic levels of anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Because orthotopic liver transplantation is associated with morbidity and mortality, it is considered a treatment of last resort. In addition, patients who already have advanced neuropathy with quadriplegia and respiratory paralysis are considered poor candidates for transplantation …”
Section: Managementmentioning
confidence: 99%